The influence of emotional stimuli on cognitive processing during transient induced mood states - Coulson, L (2012)
Selective attention is a mechanism used to allocate resources to information processing. Both mood states and emotionally salient stimuli can influence which information is selectively attended. This information is subsequently processed in a more elaborative manner and affects task performance. The experiments presented in this thesis explore the influence of mood and emotional stimuli on selective attention and consequently task performance. Mood induction procedures were used to induce transient neutral, sad, and happy mood states in healthy volunteers. A systematic review and meta-analysis of 41 studies using sad mood induction procedures showed cognitive impairments in performance in the context of task neutral stimuli. In contrast biases in attention towards mood-congruent negative stimuli led to improved task performance. A series of three behavioural experiments with 197 participants demonstrated that participants made decisions on the basis of less information when that information was preceded by emotional but not neutral stimuli. Induced mood state did not affect performance. The behavioural and neural correlates of visual attentional processing to emotional stimuli were explored using magnetoencephalography in 24 healthy participants following sad, happy, and neutral mood induction procedures. The M300, a component associated with selective attention, had greater amplitude following presentation of negative compared with positive stimuli, which was associated with improved task performance. Reduced M300 amplitude and impairments in performance occurred following sad mood induction procedures. The experiments presented in this thesis demonstrate prioritized processing of emotional information and provide some evidence for impaired performance following sad mood induction procedures.